Effects of Product Pricing, Product Packaging, and Place on Consumer Buying Behavior through Customer Satisfaction - Lejiw, Albert Dimas; Fauzi, Achmad (Technium Social Sciences Journal, 2023)
This study aims to analyze the effect of product pricing and product packaging on consumer buying behavior through customer satisfaction. This research was carried out by distributing questionnaires via Google Form to 125 respondents who are Mixue consumers in the Jakarta metropolitan area, at least 17 years old, have made at least 2 product purchases in the last six months, and know Mixue products and prices. This study used a quantitative approach by collecting data through surveys and purposive sampling. The data obtained was processed via SEM with SmartPls software. This research finds that product pricing significantly affects consumer buying behavior (p-value 0.0). Product packaging also directly and significantly influences consumer buying behavior (p-value 0.0). The place also directly and significantly influences consumer buying behavior (p-value 0.033). Customer satisfaction also directly and significantly influences consumer buying behavior (p-value 0.0). Product pricing positively and significantly influences consumer buying behavior through customer satisfaction. Product packaging positively and significantly influences consumer buying behavior through customer satisfaction (p-value 0.030). The place also positively and significantly influences consumer buying behavior through customer satisfaction (p-value 0.040).